2016
DOI: 10.1103/physrevc.94.064318
|View full text |Cite
|
Sign up to set email alerts
|

Multinucleon short-range correlation model for nuclear spectral functions: Theoretical framework

Abstract: We develop a theoretical approach for nuclear spectral functions at high missing momenta and removal energies based on the multi-nucleon short-range correlation (SRC) model. The approach is based on the effective Feynman diagrammatic method which allows to account for the relativistic effects important in the SRC domain. In addition to two-nucleon SRC with center of mass motion we derive also the contribution of three-nucleon SRCs to the nuclear spectral functions. The latter is modeled based on the assumption… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…[25], we identified this mechanism as correlation operators acting on IPM pairs in a nodeless relative S -wave that account for about 90% of the strength in the correlated part of the n [1] (p). The observation that the momentum dependence of the fat-tailed part of n [1] (p) is universal (modulo a scaling factor) is often referred to as the universality of SRC [4,24,34,35,36,37,38]. From Fig.…”
Section: Framework and Resultsmentioning
confidence: 99%
“…[25], we identified this mechanism as correlation operators acting on IPM pairs in a nodeless relative S -wave that account for about 90% of the strength in the correlated part of the n [1] (p). The observation that the momentum dependence of the fat-tailed part of n [1] (p) is universal (modulo a scaling factor) is often referred to as the universality of SRC [4,24,34,35,36,37,38]. From Fig.…”
Section: Framework and Resultsmentioning
confidence: 99%
“…Its derivation is detailed in Ref. [9,52,53]. Here, we review its incorporation into the GCF model, the results of which are shown in the main text to assess the possible impact of relativistic effects.…”
Section: Estimate Of Relativistic Effects Using the Nuclear Light-conmentioning
confidence: 99%
“…The LC formalism presented above removes this asymmetry [9]. As mentioned in the main text, while studied in detail [9,52,53] and used by previous works to analyze proton induced knockout reactions [17], the LC prescription used here to account for relativistic effects is approximate and modeldependent. The accuracy of Eq.…”
Section: Estimate Of Relativistic Effects Using the Nuclear Light-conmentioning
confidence: 99%
“…In Fig.1(b) the 3N-SRC is produced in the sequence of two short-range N N interactions in which the nucleon with the largest momentum interacts with the external probe [29,30]. The presence of short-range N N interactions in 3N-SRC configurations tells us that the recently observed pn-SRC dominance [12][13][14] is critical to our understanding of 3N-SRCs.…”
Section: N-srcs and The Pn Dominancementioning
confidence: 99%